ALGERIAN STUDENT ORGANIZATIONS IN THE ARAB LEVANT AND THEIR CONTRIBUTION TO THE LIBERATION REVOLUTION (1954-1962) - litim, Aissa (Humanities Journal of University of Zakho, 2024)
Among the goals of the Algerian Liberation Front was to emphasize the Arab identity of the struggle waged by the Algerian people, a task that the student movement in the Arab East undertook by establishing organizations for it in Syria, Egypt, Iraq, and Kuwait, which served as Algeria's permanent ambassador to these regimes and peoples. For their part, the nations showed an innate willingness to support the Algerian revolution, by opening their schools to educate the Algerian men and teaching them the foundations of modern warfare. Later, the Algerian elites who graduated from these schools and colleges contributed to supporting the structures of the revolution in its political and military aspects, and consolidating the ideological affiliation to the Algerian liberation movement, with its Arab and Islamic dimensions.